2016
DOI: 10.1016/j.heliyon.2016.e00120
|View full text |Cite
|
Sign up to set email alerts
|

Dam-Breach hydrology of the Johnstown flood of 1889–challenging the findings of the 1891 investigation report

Abstract: In 1891 a report was published by an ASCE committee to investigate the cause of the Johnstown flood of 1889. They concluded that changes made to the dam by the South Fork Fishing and Hunting Club did not cause the disaster because the embankment would have been overflowed and breached if the changes were not made. We dispute that conclusion based on hydraulic analyses of the dam as originally built, estimates of the time of concentration and time to peak for the South Fork drainage basin, and reported conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Saha et al (2019) conducted a study to address the issues of the ecosystem, sustainable management and the flow regulation impacts of dams in the Halda River in Bangladesh Coleman et al (2016). reanalyzed the 1889 Johnstown flood with a study based on hydraulic analyses of the dam as originally built, estimates of the time of concentration and time to peak for the South Fork drainage basin, and reported conditions at the dam and in the watershed Kim and Sanders (2016).…”
mentioning
confidence: 99%
“…Saha et al (2019) conducted a study to address the issues of the ecosystem, sustainable management and the flow regulation impacts of dams in the Halda River in Bangladesh Coleman et al (2016). reanalyzed the 1889 Johnstown flood with a study based on hydraulic analyses of the dam as originally built, estimates of the time of concentration and time to peak for the South Fork drainage basin, and reported conditions at the dam and in the watershed Kim and Sanders (2016).…”
mentioning
confidence: 99%
“…The 1977 peak discharge was 24,000 cfs. The 1889 discharge into the former Lake Conemaugh behind the South Fork Dam was estimated at around 7,100 cfs just before the dam overtopped ( Coleman et al., 2016 ). The 12-hour depths were the same as those used for the broader basin.…”
Section: Results: Assessment Of Major Precipitation Events Watershed ...mentioning
confidence: 99%
“…At South Fork, no discharge thresholds for flooding like those provided for East Conemaugh are provided because no gage data exist prior to 2017, although an estimate of peak discharge was made for the 1977 flood (see section 4.4 ). An estimate for inflow to the 1889 South Fork Dam prior following the severe storm is also available ( Coleman et al., 2016 ), but that value was likely obtained sometime after the peak inflow to Lake Conemaugh. It has been reported that the precipitation of May 30–31, 1889 likely had a return period of at least 100 years ( Coleman et al., 2016 ).…”
Section: Results: Assessment Of Major Precipitation Events Watershed ...mentioning
confidence: 99%
See 2 more Smart Citations